THE IMPACT OF LEARNING MANAGEMENT SYSTEM QUALITY ON STUDENT’ PERFORMANCE: THE MEDIATING ROLE OF ACTUAL USAGE - Zhang , Lixiu; Ng , Siew Foen (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
As a critical support platform for online learning, Learning Management Systems (LMS) play a vital role in modern higher education. While previous studies have confirmed a link between LMS use and academic success, the multi-stage pathways by which LMS quality affects learning performance have not been fully explored.This study employed a quantitative approach, distributing 447 questionnaires and analyzing 406 valid responses. PLS-SEM was used to examine the relationships among the variables. The results supported five hypotheses. Findings indicate that the quality of the U-Campus system positively influences perceived usefulness, which in turn is positively associated with actual usage. Moreover, actual usage significantly enhances students’ English performance.The study confirms that actual system usage mediates the relationship between U-Campus quality and English performance, highlighting the critical role of frequent system engagement in improving academic outcomes. By offering empirical evidence on how LMS quality contributes to student learning, this research adds to the growing body of literature on digital learning platforms. Future research should expand the geographic scope and incorporate system-logged usage data to further validate these findings.